The investigation of NbO2 and Nb2O5 electronic structure by XPS, UPS and first principles methods. (28th February 2013) - Weibin, Zhang; Weidong, Wu; Xueming, Wang; Xinlu, Cheng; Dawei, Yan; Changle, Shen; Liping, Peng; Yuying, Wang; Li, Bai
ABSTRACT In this paper, the electronic structures of NbO2 and Nb2O5 are theoretically and experimentally analyzed. The oxides in the samples are mainly consisted of NbO2 and NbO, whereas the outmost layer of the samples is NbO2. After exposure to air, the outermost layer on all niobium samples is Nb2O5. The photoelectrons from the first 2–4 Å contribute to the spectra, so the valence band structure of NbO2 and Nb2O5 can be confirmed from ultraviolet photoelectron spectroscopy (UPS). By comparing the UPS with density of state results, the electronic structure of NbO2 and Nb2O5 can be distinguished from each other, and then the electronic structure was deconvoluted into several electronic states. The agreement between experimental result and theory is, in the best case, satisfactory. Copyright © 2013 John Wiley & Sons, Ltd.